Advancement in analytical techniques fabricated for the quantitation of cytochrome c. (November 2022) - Yadav, Sarita; Sawarni, Neha; Kumari, Preeti; Sharma, Minakshi
Abstract: In mitochondrial electron transport chain (ETC), cytochrome c (water-soluble heme metalloprotein) transfers the electrons between cytochrome c reductase (CcR) and cytochrome c oxidase (CcO). Recently it was reported that cytochrome c acts as an in-vivo biomarker for mitochondrial damage, resuscitation, cardiac arrest, organ injury & various kinds of cancers. All these observations provide significant importance to measure the cytochrome c. Cytochrome c also acts as a mediator biomolecule of DNA damage response by its release in the cytoplasm by the mitochondria to enhance the apoptosis. Under various pathological conditions, low level or high level of cytochrome c in bloodstream can lead to various diseases at the cellular level. Diagnosis of cytochrome c levels in serum samples of patients may help to predict earlier stages as well as the severity of the disease. In healthy persons, the normal level of cytochrome c is 39.8 ng/mL. This proposed review article explains various fabricated methods for the detection of cytochrome c with their principle, merits, and demerits. Graphical Abstract: ga1 Highlights: Cytochrome c acts as an in vivo biomarker for mitochondrial damage, cardiac arrest, & non-small cell lung cancer. In healthy persons, the normal level of cyt c is 39.8 ng/mL. A portable and quick detecting mini biosensing device could be designed for Cytochrome c early biomarker.